ARTICLE REVIEW “HOW TO PREPARE A REVIEW OF AN ACADEMIC OR SCIENTIFIC ARTICLE” - Batista, Leandro Fabrício Sarmento de Oliveira (2020)
This is a review of the article entitled “How to Write a Review of an Academic or Scientific Article”. This is authored by Jonas Rodrigo Gonçalves. The article reviewed here was published in the magazine “Revista JRG de Estudos Acadêmicos” in Year III, Vol. III, n. 7, jul./dec., 2020.